Water Utilization and Land Use in the Process of Urbanization & Industrialization: the Case of Guangzhou - Mu, Rongping; Chen, Rui; Ren, Jingluan (MTT, 2005)
In order to know the real situation regarding water utilization and land use in the process of urbanization & industrialization in China, the authors first investigated rural-urban interaction in Guangzhou, especially water utilization, land use and environmental protection. Based on field visits to related plant and the departments of the Guangzhou municipal government, and observations concerning water utilization and land use in the process of urbanization and industrialization of Guangzhou, the authors analyse the problems and policy issues related to water utilization, land use and environmental protection, and evaluate the implementation of policies issued by both central government and local government, and try to give some recommendations for resolving the conflicts between economic requirements, the limited resources, and environmental protection.
Keywords: Ys; water utilization; land use; urbanization; industrialization; Guangzhou